Insulin resistance in health and disease: exploring the role of disuse skeletal muscle atrophy, testosterone and Beta-Hydroxy-Beta-Methylbutyrate (HMB) in young and older men - Shanthaveerappa Rudrappa, Supreeth (2021)
Background